Porphyrin-based covalent organic polymer by inverse electron demand Diels-Alder reaction - Cetinkaya, Ahmet; Sadak, Ali Enis; Ayhan, Mehmet Menaf; Zorlu, Yunus; Kahveci, Muhammet U. (Pergamon-Elsevier Science Ltd, 2021)
Inverse electron demand Diels-Alder (IEDDA) reaction has been employed as a powerful ligation in several fields. In the current work, a synthetic approach relying on IEDDA reaction is developed for preparation of a porphyrin based covalent organic polymer (PoTz-COP). A tetra-norbornene functional porphyrin is chosen as the core and a bis-tetrazine as the linker. The PoTz-COP is readily formed by just mixing the components without a catalyst and under mild conditions. Chemical structure, morphology (XRD, SEM-EDX), porosity (BET), thermal stability (TGA), optical and gas sorption (CO2 uptake) and selectivity (CO2/N-2) properties via Myers and Prausnitz's ideal adsorbed solution theory (IAST) are investigated. PoTz-COP shows remarkably high adsorption selectivity of CO2 over N-2 as found 80, 42, and 47 at 50/50 ratio; 84, 39 and 40 at 15/85 ratio; and 84, 39 and 38 at 05/95 ratio at temperatures of 273 K, 298 K and 320 K at 1.1 bar pressure respectively. The optical band gap is determined relatively narrow as 1.66 eV.
Keywords: Inverse electron demand Diels-Alder reaction; Tetrazine; Covalent organic polymer; Gas sorption; Selectivity